2020
DOI: 10.1002/epi4.12409
|View full text |Cite
|
Sign up to set email alerts
|

COX‐2/PGE2 axis regulates hippocampal BDNF/TrkB signaling via EP2 receptor after prolonged seizures

Abstract: Objective The objective of this study was to identify the signaling pathway that is immediately triggered by status epilepticus (SE) and in turn contributes to the excessive brain‐derived neurotrophic factor (BDNF)/tropomyosin‐related kinase receptor B (TrkB) signaling within the hippocampus. Methods We used quantitative PCR, enzyme‐linked immunosorbent assay, and Western blot analysis to examine gene expression at both mRNA and protein levels in the hippocampus following prolonged SE in mice and rats. Three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 52 publications
2
34
0
Order By: Relevance
“…Recent findings suggest that COX-2 via PGE2/EP2 signaling regulates the hippocampal BDNF/TrkB pathway following prolonged seizures. Thus, EP2 inhibition by brain-permeable antagonists such as TG6-10-1 might provide a novel strategy to suppress the abnormal TrkB activity, an event that can trigger epileptogenesis and consequently generate epilepsy [ 582 ].…”
Section: Other Potential Therapeutic Targets To Considermentioning
confidence: 99%
“…Recent findings suggest that COX-2 via PGE2/EP2 signaling regulates the hippocampal BDNF/TrkB pathway following prolonged seizures. Thus, EP2 inhibition by brain-permeable antagonists such as TG6-10-1 might provide a novel strategy to suppress the abnormal TrkB activity, an event that can trigger epileptogenesis and consequently generate epilepsy [ 582 ].…”
Section: Other Potential Therapeutic Targets To Considermentioning
confidence: 99%
“…In this work, 7 we showed that cyclooxygenase‐2 (COX‐2) and BDNF in the hippocampus were rapidly upregulated in very similar time‐dependent manners after the onset of SE, while the induction of COX‐2 temporally and quantitatively led that of BDNF. Blocking COX‐2 enzymatic activity by selective inhibitor prevented BDNF elevation in the hippocampus following SE.…”
Section: What Were the Results And How Do You Interpret Your Findings?mentioning
confidence: 93%
“…As a conventional intracellular second messenger, cAMP binds and activates protein kinase A (PKA) to regulate pleiotropic effects. As such, the cAMP‐activated PKA subsequently translocates to the cell nucleus, where it acts on transcription factors including the cAMP‐responsive element‐binding protein (CREB) 67 . The activated CREB in turn binds to CRE sites to regulate the expression of genes that are involved in the neuronal plasticity and regeneration 68 .…”
Section: Gs‐coupled Prostanoid Receptorsmentioning
confidence: 99%